2012
DOI: 10.4172/2155-6121.s2-003
|View full text |Cite
|
Sign up to set email alerts
|

To Assess the Quality of Life (QOL) of Caregivers and Patients Suffering from Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Rationale: Chronic Obstructive Pulmonary Disease (COPD) is associated with physical and psychological burdens. The impact of disease has been studied on patients but it also has a profound and pervasive effect on family and friends resulting in psychological strain, social isolation, relationship strains and financial strains from the added responsibilities of managing the patients. Few studies have found a significant burden on both caregivers and patients alike, but the data from the Indian setup in lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Majority of the caregivers in both groups were males (63.8% and 57.4%). This finding contrasts with similar studies that showed a majority of the caregivers of children with chronic diseases to be females [27] [28]. Furthermore, majority of the caregivers in both groups The overall QOL for respondents whose children do not have TB appears to be higher (mean 7.87 and SD 1.84) compared with respondents whose children have TB (mean 6.85 and SD 1.37).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Majority of the caregivers in both groups were males (63.8% and 57.4%). This finding contrasts with similar studies that showed a majority of the caregivers of children with chronic diseases to be females [27] [28]. Furthermore, majority of the caregivers in both groups The overall QOL for respondents whose children do not have TB appears to be higher (mean 7.87 and SD 1.84) compared with respondents whose children have TB (mean 6.85 and SD 1.37).…”
Section: Discussioncontrasting
confidence: 92%
“…These findings suggest that respondents whose children have TB have impaired QOL compared with those whose children do not have TB. This is consistent with the findings of several studies that measured the QOL of adult caregivers whose children suffered from chronic diseases such as osteogenesis imperfecta [27], sickle cell disease [31], cancer [32] [33], disabilities, Down's syndrome [34], speech and language disorders [35], COPD [28], and schizophrenia [36]. All these studies revealed that the caregivers of the diseased children had impaired QOL compared with control populations.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover caring for patients with chronic and disabling disease is associated with the caregivers' experiencing physical and psychological distress, limitations to their personal and social activities, and financial burden [5]. Especially the experience of a wife caregiver has been described as a mixture of anger, helplessness, guilt and isolation and was deemed to have lost freedom, because they had relinquished recreational and social activities [6].…”
Section: Introductionmentioning
confidence: 99%
“…Family caregiving refers to unpaid relatives or friends of a disabled individual who help that individual with his or her activities of daily living. The words may be prefixed with ‘family’ ‘spousal’, ‘child’, ‘parent’, ‘young’ or ‘adult’ (Kumar, Matreja, Gupta, Singh, & Garg, ).…”
Section: Introductionmentioning
confidence: 99%